PENERAPAN SKEMA BUY THE SERVICE PADA ANGKUTAN PERDESAAN DI KABUPATEN KOTABARU (FSTPT Indonesia, 2023)
The availability of public transportation is a major factor in facilitating, supporting, and enhancing development both at the regional and national levels as well as the welfare of the people. The transportation sector in Kotabaru Regency has several problems with public transportation services which are currently not optimal. Broadly speaking, the reasons for the low public interest in public transportation are that the services provided are still far from expectations and are not in accordance with minimum service standards, such as the vehicles used do not pay attention to safety aspects, there is no definite service schedule and information related to public transportation is not yet available. easily accessible. One of the steps that can be taken by the Kotabaru Regency government is to establish a policy or program called